Association of maternal pre-pregnancy weight, weight gain during pregnancy, and smoking with small-for-gestational-age infants in Japan. (January 2016) - Akahoshi, Emi; Arima, Kazuhiko; Miura, Kiyonori; Nishimura, Takayuki; Abe, Yasuyo; Yamamoto, Naoko; Oishi, Kazuyo; Masuzaki, Hideaki; Aoyagi, Kiyoshi
Abstract: Aim: The aim of this study was to evaluate the associations of maternal pre-pregnancy body mass index (BMI), weight gain during pregnancy, and smoking, with small-for-gestational-age (SGA) births among Japanese women. Materials and methods: Subjects were pregnant women who gave birth to single, term infants (37–42 weeks) at a clinic and hospital in the Nagasaki area between 2012 and 2013. To examine associations with SGA, 49 underweight (BMI < 18.5 kg/m 2 ) and 579 normal-weight (18.5 ≤ BMI < 25.0 kg/m 2 ) Japanese women with either appropriate-for-gestational-age or SGA infants were selected and analyzed. Results: The prevalence of SGA infants was 6.8%. Seven percent of women were current smokers. Prevalence of pre-pregnancy underweight and gestational weight gain less than recommendation were 20.8% and 16.7%, respectively. Multivariate logistic regression was performed to assess factors affecting SGA infants in the pregnant women. After adjusting for covariates, the amount of maternal weight gain below recommendation (odds ratio (OR), 2.72; 95% confidence interval (CI), 1.37–5.39) and maternal smoking status (OR, 2.80; 95% CI, 1.14–6.91) were significantly and independently associated with SGA births. Pre-pregnancy maternal weight status showed a borderline association (OR, 1.91; 95% CI, 0.96–3.83, p = 0.067). Conclusion: To prevent SGA births, education regarding the adequate nutrition and the adverse effect of maternal smoking is important for the women of reproductive age. Highlights: Low maternal weight gain was significantly associated with SGA birth. Maternal smoking status was significantly associated with SGA birth. Adequate BMI before conception is an important factor for preventing SGA births As prevention of SGA births, education of the adequate nutrition might be important.